Influence of Satisfaction of AKM Simulation Exam Participants at SMP Negeri 4 Tanjungbalai Using the PLS-SEM Model - Marnida Yusfiani; Ahyani Ridhyani Lubis; Awan Muchsin Harahap (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah - 1, 2022)
In the post-COVID-19 era, the government continues to move so that education continues to run with facilities and infrastructure as one of the supporting factors. Quality improvement is very important to increase the quality and quantity that exists in the form of literacy and numeracy as a form of basic understanding to evaluate the form of texts and problems that exist in society. The Minimum Competency Assessment (AKM) is a type of quality improvement for both students and schools. For SMP 4, Tanjungbalai City, which conducted the AKM Simulation Exam with a total student population of 42 people in class VIII, To carry out this research, the PLS-SIM model was carried out to determine the analysis of the influence of student satisfaction on taking the simulation exam. From the data obtained and data processing carried out, the results of the validation show an average value of AVE student satisfaction of 0.638, an R Square value of 0.844, an adjusted R Square value of 0.831, and a T-Statistic value of 1.049 for users, a T-Statistic of 4.947 for testing, and a T-Statistic of 1.672 for network system